Polyketides From the Endophytic Fungus Cladosporium sp. Isolated From the Mangrove Plant Excoecaria agallocha - Wang, Liping; Han, Xiuli; Zhu, Guoliang; Wang, Yi; Chairoungdua, Arthit; Piyachaturawat, Pawinee; Zhu, Weiming (Frontiers in Chemistry, 2018)
Five new polyketides (2–6) and ten known compounds (1 and 7–15) were obtained from the fermentation products of the endophytic fungus Cladosporium sp. OUCMDZ-302 with the mangrove plant, Excoecaria agallocha (Euphorbiaceae). The new structures of 2–6 were established on the basis of ECD, specific rotation and spectroscopic data as well as the chemical calculation. Compound 7 showed cytotoxicity against H1975 cell line with an IC50 value of 10.0 μM. Compounds 4 and 8–10 showed radical scavenging activity against DPPH with the IC50 values of 2.65, 0.24, 5.66 and 6.67 μM, respectively. In addition, the absolute configuration of compound 1 was solidly determined by X-ray and sugar analysis of the acidic hydrolysates for the first time as well as those of compounds 8–10 in this paper.